The Influence of TikTok Content Information on Fulfilling Information Needs (A Study on the @buiramira Account by Library and Information Science Students, Class of 2020 - Asrianti, Fadhilah; Nabila, Jeihan (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This research aims to describe the influence of TikTok content information on fulfilling information needs (study of the @buiramira account by library and information science students class of 2020). This research was conducted using descriptive methods with a quantitative research type. This research consists of two variables, namely social media (X) and information need variables (Y). The population of this research is library and information science students class of 2020. A sample of 50 was taken using the Slovin formula with a precision of 10%. The technique used is purposive sampling. Based on the research results, it is known that social media has a positive and significant effect on information needs. The social media variable (X) influences information needs (Y) by 46%, while the remaining 54% is influenced by other factors not examined in this research.